"Rose is a rose is a rose is a rose" – what about code and law?. Issue 4 (August 2018) - Weber, Rolf H.
Abstract: Law and information technology are interlinked. Since Lessig's "code is law" the discussions address the viability of law in technology markets. But recently, the direction of view has changed by way of conversion; in the context of smart contracts, the notion "law is code" became prevalent. The contribution looks into the interdependencies between law and code and pleads for a new functional understanding of law.